2018
DOI: 10.1007/s00436-018-5855-1
|View full text |Cite
|
Sign up to set email alerts
|

Chemical analysis and giardicidal effectiveness of the aqueous extract of Cymbopogon citratus Stapf

Abstract: CcAE (25, 50, 100, 200, 400, and 500 μg/ml) was in vitro incubated with G. lamblia trophozoites in comparison with metronidazole (MTZ 10 and 25 μg/ml). Growth inhibition was evaluated after 3, 24, and 48 h of drug exposure. Infected groups of mice were orally treated for 7 days with CcAE at 125, 250, and 500 mg/kg/day/mouse, in comparison with a group treated with 15 mg/kg/day/mouse MTZ for the same period. The total phenolic components (TPC), the total flavonoid components (TFC), the 2,2,diphenyl-1-picrylhydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…These studies showed the potential for prevention or control of growth of the populations of these parasites. However, only a few studies have been published, despite the potential of this plant (Macedo et al, 2015;Chukwuocha et al, 2016;Limoncu et al, 2017;Méabed, et al, 2018;Macedo et al, 2019).…”
Section: Experimental Workmentioning
confidence: 99%
“…These studies showed the potential for prevention or control of growth of the populations of these parasites. However, only a few studies have been published, despite the potential of this plant (Macedo et al, 2015;Chukwuocha et al, 2016;Limoncu et al, 2017;Méabed, et al, 2018;Macedo et al, 2019).…”
Section: Experimental Workmentioning
confidence: 99%
“…The essential oil from C. citratus is known as lemongrass oil, with citral as the major component [12]. Lemongrass oil is reported to possess a variety of pharmacological properties including antiparasitic [13], antioxidant [14], antimicrobial [12], and anti-inflammatory [15]. Lemongrass oil was also reported to show miticididal effect against a plant pathogen (Tetranycchus urticae) [16] and house dust mites [17].…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the risks of using chemical drugs, the World Health Organization (WHO) has proposed the use of medicinal plants and other natural products and reports that approximately 80% of the world population use traditional remedies for health care (Anquez-Traxler, 2011). Up to now, ethnobotanical and ethnopharmacological investigations disclose a variety of natural products used for the treatment of Giardiasis which has had a variety of effects (Rahimi-Esboei et al ., 2013 a , 2013 b ; Derda and Hadaś, 2014; Méabed et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%